Business Mentoring as Experiential Learning through the BRIDGE Model - Rahmat Ramli; Sylvia Sari Rosalina (Economics and Business Journal (ECBIS), 2026)
The persistent gap between theoretical instruction and real-world practice remains a critical challenge in business education, particularly in contexts involving Micro, Small, and Medium Enterprises (MSMEs). Experiential learning has been promoted as a pedagogical response to this challenge; however, many initiatives lack structured frameworks that integrate student learning with meaningful community engagement. This study examines the implementation of the BRIDGE model (Build, Reach, Discover, Grow, and Elevate) as a structured business mentoring approach grounded in experiential learning principles. Using a qualitative participatory action research design, the study involved 15 undergraduate business students and five MSMEs in Semarang City, Indonesia. Data were collected through participant observation, in-depth interviews, focus group discussions, reflective journals, and program documentation, and analyzed using thematic analysis. The findings indicate that the BRIDGE model facilitates deep experiential learning by enabling students to connect theoretical concepts with contextual business realities, while simultaneously generating instrumental and symbolic benefits for MSME partners. Despite limitations related to program duration, the model demonstrates strong potential as a feasible and transferable framework for experiential business education in emerging economy contexts.